Benefits and Students’ Perception on Role-Play Teaching Technique: Progressive & Fun Learning Experiences in Brunei - Norazmie Yusof; Yabit Alas (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2021)
This paper presents a preliminary study on the teaching and learning of one of Brunei ethnic languages at The Language Centre, Universiti Brunei Darussalam (LCUBD henceforth). Dusun language is one of the ethnic languages still spoken in Brunei and is considered an endangered ethnic language. Research has shown that the usage of this language has been decreasing in recent decades due to factors such as migration and language choice. LCUBD has taken proactive measures by offering Dusun language as one of the elec-tive courses at the center. This study aimed to identify the benefits of using role-play in learning Dusun language and identify students’ perception of role-play activities in Dusun language class. Likert scale ques-tionnaires and open-ended questions were employed to collect data on 71 students who were enrolled in the LY-1433 Dusun I (basic) course. The result of the study suggested that role-play activity was suitable for the students, fun and entertaining, and could increase their confidence Apart from that a positive student-teacher relationship also played a big role during the learning process of ethnic language. Overall, role-play can be recommended as one of the teaching techniques to teach minority ethnic language.